Установка для измерения удельного коэффициента силы света материалов со световозвращающим эффектом - Butenko, V. K.; Dobrovolskiy, Yu. G.; Shabashkevich, B. G.; Yuriev, V. G. (PE "Politekhperiodika", Book and Journal Publishers, 2009)
The installation for measuring of specific coefficient of candle-power light of returning surfaces on the accordance of ДСТУ 4100-2002 is developed. The construction of installation provides more wide in comparison with analogues range of measuring — from 10–1 to 104 kd/(lk·m2). Limit of the basic assumed relative error of measuring is no more than ±15%.